Labor leverage, coordination failures, and aggregate risk - Bouvard, Matthieu; de Motta, Adolfo (Journal of Financial Economics, 2021)
This paper studies an economy in which demand spillovers make firms’ production decisions strategic complements. Firms choose their operating leverage trading off higher fixed costs for lower variable costs. Operating leverage governs firms’ exposures to an aggregate labor productivity shock. In equilibrium, firms exhibit excessive operating leverage because they do not internalize that an economy with higher aggregate operating leverage is more likely to fall into a recession following a negative productivity shock. Welfare losses coming from firms’ failure to coordinate production are amplified by suboptimal risk-taking, which magnifies the impact of productivity shocks onto aggregate output.